Adsorption Isotherm Studies of Rhodamine B on Citrus sinesis Peel - Purwiandono, Gani; Lestari, Puji; Widodo, Wahyu; Marlina, Marlina; Aprilia, Nadia (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2017)
Adsorption of Rhodamine B on Citrus sinesis peel biosorbent has been conducted. The adsorption process was carried out in neutral pH for 90 min. The active surface of the Citrus sinesis peel biosorbent was 15 m2/g and the density was 0.52 g/cm3. The adsorption mechanism of Rhodamine B on Citrus sinesis peel biosorbent was studied using 4 adsorption model; Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich. The adsorption fitted the Freundlich model with the regression value of 0.906. This indicates that the adsorption of Rhodamine B on the surface of Citrus sinesis peel biosorbent was a multilayer interaction.